Chronic circadian misalignment accelerates sarcopenia progression in mice - Seya, Takashi; Koike, Nobuya; Okubo, Naoki; Umemura, Yasuhiro; Tsuchiya, Yoshiki; Yabumoto, Kazuya; Endo, Yasuhiro; Iinuma, Kanako; Kakibuchi, Akiyo; Sugimoto, Akira; Takahashi, Kenji; Yoo, Seung-Hee; et al. (Frontiers in Physiology, 2025)
IntroductionIn today’s 24/7 society, circadian misalignment caused by environmental and lifestyle factors is associated with various adverse health consequences. Understanding tissue-specific pathology is required to counter this growing public health challenge. A potential association of environmental circadian misalignment with sarcopenia, or accelerated loss of skeletal muscle strength and mass, is poorly documented.Methods14-week-old wild-type C57BL/6J male mice were exposed to a chronic jet lag (CJL) paradigm consisting of an 8-h phase advance every 4 days (the ADV group) or a fixed light-dark cycle (the LD group) for 64 weeks. Grip strength was measured during the experiment, and hindlimb muscle weight was assessed after the 64-week CJL. In addition, transcriptomic and histological analysis of the hindlimb muscles were performed in all animals.ResultsADV mice exhibited significant reductions in grip strength and muscle weight relative to LD mice. Transcriptomic and histological analyses showed activation of TWEAK/Fn14 signaling and reduced myofiber cross-sectional area, hallmark features of sarcopenia, in the ADV group. Somewhat surprisingly, ADV mice showed increased centrally nucleated fibers, myosin heavy chain co-expressing fibers, and myogenic gene expression, suggesting that compensatory muscle regeneration and remodeling processes are activated but remain insufficient to counter muscle atrophy.ConclusionThese findings demonstrate that circadian misalignment is a potential risk factor for sarcopenia, underscoring circadian rhythms as a key regulator and actionable target for sarcopenia prevention.